Ecologically valid carbohydrate intake during soccer-specific exercise does not affect running performance in a fed state - Funnell, M. P.; Dykes, N. R.; Owen, E. J.; Mears, S. A.; Rollo, I.; James, L. J. (Nutrients, 2017)
This study assessed the effect of carbohydrate intake on self-selected soccer-specific running performance. Sixteen male soccer players (age 23 ± 4 years; body mass 76.9 ± 7.2 kg; predicted VO2max = 54.2 ± 2.9 mL·kg-1·min-1; soccer experience 13 ± 4 years) completed a progressive multistage fitness test, familiarisation trial and two experimental trials, involving a modified version of the Loughborough Intermittent Shuttle Test (LIST) to simulate a soccer match in a fed state. Subjects completed six 15 min blocks (two halves of 45 min) of intermittent shuttle running, with a 15-min half-time. Blocks 3 and 6, allowed self-selection of running speeds and sprint times, were assessed throughout. Subjects consumed 250 mL of either a 12% carbohydrate solution (CHO) or a non-caloric taste matched placebo (PLA) before and at half-time of the LIST. Sprint times were not different between trials (CHO 2.71 ± 0.15 s, PLA 2.70 ± 0.14 s; p = 0.202). Total distance covered in self-selected blocks (block 3: CHO 2.07 ± 0.06 km; PLA 2.09 ± 0.08 km; block 6: CHO 2.04 ± 0.09 km; PLA 2.06 ± 0.08 km; p = 0.122) was not different between trials. There was no difference between trials for distance covered (p = 0.297) or mean speed (p = 0.172) for jogging or cruising. Blood glucose concentration was greater (p < 0.001) at the end of half-time during the CHO trial. In conclusion, consumption of 250 mL of 12% CHO solution before and at half-time of a simulated soccer match does not affect self-selected running or sprint performance in a fed state.